Drone in NBC disaster - Kim, Yong Han (International Journal Of Community Medicine And Public Health, 2018)
Nuclear, Biological and chemical disasters are tragic and should never happen. Unavoidably occurred, access and reach are difficult because rescue personnel are exposed to hazards. Drone is an unmanned aerial vehicle that can be operated by remote control or autonomous aviation. It has some advantages in NBC disaster as followings: First, drone can take a picture and record the scene in contaminated zone. Communication with injured is also possible without exposure to rescue team. Triage can be performed by analysis of movement, breathing and responsiveness, etc. Second, atropine and oxime are essential to nerve agent poisoning. It can be delivered by drone only inside contaminated zone for survivors. Third, drone can collect specimen without human exposure. Investigator can analyze the extent of pollution in remote laboratory with this specimen. Fourth, survivor can be evacuated from disaster area by drone itself. This operation needs heavy capability that would lift patients. I hope that NBC disaster could be overcome with this useful modern convenience.